Cellular senescence: from homeostasis to pathological implications and therapeutic strategies - Li, Chunhong; Yuan, Yixiao; Jia, YingDong; Zhou, Qiang; Wang, Qiang; Jiang, Xiulin (Frontiers in Immunology, 2025)
Cellular aging is a multifactorial and intricately regulated physiological process with profound implications. The interaction between cellular senescence and cancer is complex and multifaceted, senescence can both promote and inhibit tumor progression through various mechanisms. M6A methylation modification regulates the aging process of cells and tissues by modulating senescence-related genes. In this review, we comprehensively discuss the characteristics of cellular senescence, the signaling pathways regulating senescence, the biomarkers of senescence, and the mechanisms of anti-senescence drugs. Notably, this review also delves into the complex interactions between senescence and cancer, emphasizing the dual role of the senescent microenvironment in tumor initiation, progression, and treatment. Finally, we thoroughly explore the function and mechanism of m6A methylation modification in cellular senescence, revealing its critical role in regulating gene expression and maintaining cellular homeostasis. In conclusion, this review provides a comprehensive perspective on the molecular mechanisms and biological significance of cellular senescence and offers new insights for the development of anti-senescence strategies.